2012
DOI: 10.4067/s0718-95162012005000033
|View full text |Cite
|
Sign up to set email alerts
|

Bio-diesel waste as tailored organic fertilizer for improving yields and nutritive values of Lycopercicum esculatum (tomato) crop

Abstract: The present study focused on utilization of the de-oiled Jatropha cake, a bio-waste from the bio diesel extraction process, as organic fertilizer. Tomato crop was subjected to different treatments comprising varying composition of the Jatropha cake fertilizer, applied at varying age of plant life-cycle. The impact on yield, morphological and nutritional parameters was studied. Results revealed that an optimal (2-3 % by weight) dose applied on the soil at the time of onset of flowering (around 45 days), signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…Similar findings were reported by Chaturvedi et al (2008). According to a field experiment conducted by Chand et al (2006), it was found that integrated supply of plant nutrients through FYM (farmyard manure) and fertilizer, N, P, and K along with Sesbania green manuring played a significant role in sustaining soil fertility and crop productivity.…”
Section: Introductionsupporting
confidence: 87%
“…Similar findings were reported by Chaturvedi et al (2008). According to a field experiment conducted by Chand et al (2006), it was found that integrated supply of plant nutrients through FYM (farmyard manure) and fertilizer, N, P, and K along with Sesbania green manuring played a significant role in sustaining soil fertility and crop productivity.…”
Section: Introductionsupporting
confidence: 87%
“…The addition of organic wastes to these soils is a current environmental and agricultural practice for maintaining soil quality. It has a greatest effect on organic matter content and nutrient values, as well as improves the structure, water and air balance and microbiological activities of soils (Candemir and Gulser, 2007;Chaturvedi et al, 2008). Therefore, the application of organic wastes to these soils that are used for crop production is of great importance for soil productivity due to their nutritional input and low costs; (Cogger et al, 2004;Mantovi et al, 2005;Sigua et al, 2005. As the soil organic matter increases, nitrogen (N) and phosphorus (P) availability in the soil increases (Ewulo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive and widespread use of inorganic fertilizers and pesticides adversely affects the soil environment, leading to decreased crop productivity and production of potentially harmful food, unsafe for human consumption. These unintended harmful effects and the energy intensive processes involved in the production of inorganic fertilizers have resulted in several research initiatives for developing organic fertilizer alternatives (Chaturvedi and Kumar, 2012).…”
Section: Introductionmentioning
confidence: 99%